2024
DOI: 10.1002/ente.202301142
|View full text |Cite
|
Sign up to set email alerts
|

Structural Optimization of Reactor for the Enhancement of CO2 Electrochemical Reduction Based on Gas–Liquid Mixing Flow Model

Haolin Ye,
Xiaoxu Xuan,
Mengjie Wang
et al.

Abstract: The CO2 electrochemical reduction reaction (CO2ERR) is heralded for carbon dioxide and renewable energy utilization. However, complexities in catalyst optimization and reactor structure research hinder its practical application. Herein, rather than traditional catalyst optimization, emphasis is placed on refining the reactor structure to enhance gas–liquid mixing. The goal is to raise the CO2 concentration in the reaction zone and extend its residence refining CO2ERR. Building on prior reactor designs, this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Additionally, considering the existence of an inlet elbow, transmission shaft, and other structural components, the inflow conditions during the reverse operation of axial-flow pumps are poor, resulting in reduced uniformity in fluid distribution within the impeller's front section. The formation of non-uniform inflow induces an imbalance in impeller forces, increasing the complexity of internal flow inside the PAT [10][11][12]. This leads to poor stability of the axial PAT with lower efficiency, vibrations, and a limited high-efficiency range [13,14], presenting a substantial menace to the secure and stable operation of hydraulic machinery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, considering the existence of an inlet elbow, transmission shaft, and other structural components, the inflow conditions during the reverse operation of axial-flow pumps are poor, resulting in reduced uniformity in fluid distribution within the impeller's front section. The formation of non-uniform inflow induces an imbalance in impeller forces, increasing the complexity of internal flow inside the PAT [10][11][12]. This leads to poor stability of the axial PAT with lower efficiency, vibrations, and a limited high-efficiency range [13,14], presenting a substantial menace to the secure and stable operation of hydraulic machinery.…”
Section: Introductionmentioning
confidence: 99%
“…It was revealed that non-uniform inflow resulted in increased impeller axial force fluctuations, pressure pulsation levels, and hydraulic losses, potentially contributing to a subsequent reduction in pump head and efficiency [20][21][22]. Meng et al [10] analyzed the impact of non-uniform inflow within a vertical axial-flow pump and found that the increasing inflow non-uniformity would increase the stress of the impeller, consequently raising the risk of failure due to fatigue. In a study conducted by Wang et al [23,24], research results showed that the reduced uniformity of inflow resulted in a decrease in pump head and operational efficiency, which made the flow inside the impeller more complex and impeller forces more unbalanced.…”
Section: Introductionmentioning
confidence: 99%